Disrupted Regional Cerebral Blood Flow and Functional Connectivity in Pontine Infarction: A Longitudinal MRI Study - Wei, Ying; Wu, Luobing; Wang, Yingying; Liu, Jingchun; Miao, Peifang; Wang, Kaiyu; Wang, Caihong; Cheng, Jingliang (Frontiers in Aging Neuroscience, 2020)
Abnormal cerebral brain flow (CBF) and resting-state functional connectivity (rs-FC) are sensitive biomarkers of disease progression and prognosis. This study inves-tigated neural underpinnings of motor and cognitive recovery by longitudinally studying the changes of CBF and FC in pontine infarction (PI). Twenty patients un-derwent three-dimensional pseudo-continuous arterial spin labeling (3D-pcASL), resting-state functional magnetic resonance imaging (rs-fMRI) scans, as well as be-havioral assessments at 1 week, 1 month, 3 months, and 6 months after stroke. Twenty normal control (NC) subjects underwent the same examination once. First, we investigated CBF changes in the acute stage, and longitudinal changes from 1 week to 6 months after PI. Brain regions with longitudinal CBF changes were then used as seeds to investigate longitudinal FC alterations during the follow-up period. Compared with NC group, patients in the left PI (LPI) and right PI (RPI) groups showed significant CBF alterations in the bilateral cerebellar posterior lobe and some supratentorial brain regions at the baseline stage. Longitudinal analysis re-vealed that altered CBF values in the right supramarginal (SMG_R) for the LPI group, while the RPI group showed significantly dynamic changes of CBF in the left calcarine sulcus (CAL_L), middle occipital gyrus (MOG_L), right supplementary motor area (SMA_R). Using the SMG_R as the seed in the LPI group, FC changes were found in the MOG_L, middle temporal gyrus (MTG_L) and prefrontal lobe (IFG_L). Correlation analysis showed that longitudinal CBF changes in the SMG_R and FC values between the SMG_R and MOG_L were associated with motor and memory scores in the LPI group, and longitudinal CBF changes in the CAL_L and SMA_R were related to memory and motor recovery in the RPI group. These longi-tudinal CBF and accompany FC alterations may provide insights into the neural mechanism underlying functional recovery after PI, including that of motor and cognitive functions.